2023
DOI: 10.3390/jcm12020597
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Sour Taste Is the Striking Feature among Four Basic Taste Qualities in Tunisian COVID-19 Patients

Abstract: Background: Taste disorders (TDs) have been reported to be very common in patients suffering from coronavirus disease 2019 (COVID-19), which is caused by the SARS-CoV-2 virus. In most of the hitherto conducted studies, a gustatory assessment was performed on the basis of surveys or self-reports by patients. The aim of our study was to undertake an objective assessment of four basic taste qualities by conducting tasting sessions that allowed detection thresholds in COVID-19 Tunisian patients and to study their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
2
1
Order By: Relevance
“…Ageusia and specific ageusia, which are rare conditions, were found in almost one-third of the patients. In this study, specific ageusia for bitter, salt, sour and sweet taste was found, consistent with other studies 39 , 40 . Findings from the present study revealed that about one-fifth of post-COVID-19 patients had no bitter taste sensation, about one-tenth had no salt or sour taste sensation, and only one patient reported no sensation for sweet taste.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Ageusia and specific ageusia, which are rare conditions, were found in almost one-third of the patients. In this study, specific ageusia for bitter, salt, sour and sweet taste was found, consistent with other studies 39 , 40 . Findings from the present study revealed that about one-fifth of post-COVID-19 patients had no bitter taste sensation, about one-tenth had no salt or sour taste sensation, and only one patient reported no sensation for sweet taste.…”
Section: Discussionsupporting
confidence: 93%
“…Findings from the present study revealed that about one-fifth of post-COVID-19 patients had no bitter taste sensation, about one-tenth had no salt or sour taste sensation, and only one patient reported no sensation for sweet taste. While in the present study, bitter taste ageusia was most common, other studies have reported specific ageusia for sour taste as the most prevalent 39 , 40 . Loss of perception of bitter taste may have serious implications as bitter taste warns about ingestion of potentially harmful, toxic, or poisonous chemical substances 57 .…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…One well-known sign of COVID-19, reported in about 40% of SARS-CoV-2 positive individuals, is the loss of taste, and, interestingly, a strong positive correlation has been reported between SARS-CoV-2 RNA in the saliva and patients' self-reported "loss of taste" in symptomatic individuals [155,156]. There have been two patients to date who have reported taste abnormalities linked to a high viral load in their saliva and a considerable epithelial (pCK+) cell infection in ACE2-expressing cells [27].…”
Section: Oc Pathologies Triggered By Covid-19mentioning
confidence: 99%
“…The third plausible mechanism could be through a direct infection and damage to the cranial nerves responsible for taste sensation, such as the facial nerve, the glossopharyngeal nerve, and the vagus nerve [11]. Some studies reported that patients with COVID-19 suffered from sour and salty taste suppression more severely than bitter and sweet tastes, and suggested that the differences were due to the former two taste qualities being transmitted by ion channels whereas the latter were by transduction via G-protein-coupled receptors [12,13]. Regardless of the pathogenesis, ageusia could have serious implications for the well-being of the affected patients, as a recent study showed that COVID-19-related ageusia might increase the risk of depression and suicidal ideation by 30% [14].…”
Section: Introductionmentioning
confidence: 99%